Experimental study of the potential for thermal energy recovery with thermoelectric devices in low displacement diesel engines. Issue 11 (November 2021) - Ramírez-Restrepo, R.; Sagastume-Gutiérrez, A.; Cabello-Eras, J.; Hernández, B.; Duarte-Forero, J.
Abstract: Improving the thermal efficiency of internal combustion engines is essential to reduce the operating costs and complaints with the increasing environmental requirements. Thermoelectric generators came up as an opportunity to reuse part of the heat loss with the exhausts. This paper evaluates the performance of a thermoelectric generator to improve the efficiency of a stationary diesel engine under different rotational speeds and torques. The data was obtained through CFD simulations and validated with experiments. The proposed solution uses a cooling system to control the temperature of the thermoelectric modules. The results show that the torque and the rotational speed of the engine are the most significant performance parameters of the thermoelectric generator, while the influence of the cooling water temperature has a minor but still significant influence. Additionally, the results show a change from 1.3% to 6.2% in the thermoelectric generator efficiency, while the exergy efficiency varies between 1.8% and 7.9%. The exergy balance indicates that most of the exergy is loss because of the irreversibilities in the thermoelectric generator and of the exergy loss with the exhausts. The exergy loss can be reduced by optimizing the design of the heat exchanger. Since the thermoelectric generator improved the engine efficiency by a marginal 0.2%–0.8%. Therefore, it is important to further research how to improve the design of heat exchangers for thermoelectric generators to increase their energy conversion efficiency and their impact on the energy efficiency of internal combustion engines. Abstract : Energy efficiency; internal combustion engine; thermoelectric generator; thermoelectric module.